Alexithymia in anorexia nervosa: the mediating role of depression - Torres, Sandra (2015)
The role of depression in the expression of alexithymia in anorexia nervosa (AN) has been controversially explained and several variables that may mask or increase the presence of emotional difficulties have scant examination in previous studies. This study aims to analyze the associations between alexithymia and state variables, such as age, BMI, illness duration, treatment duration, and medication status in AN participants, and to test the mediating role of depression in emotional difficulties. The Toronto Alexithymia Scale (TAS-20) and the Zung Self-Rating Depression Scale were administrated to 160 females: 80 participants with AN and 80 healthy controls. High levels of alexithymia were not a function of state variables. The mediating role of depression differed by the alexithymia dimension, with total mediation found for the TAS-DDF and partial mediation found for the TAS-DIF. Alexithymia is a relevant feature throughout the spectrum of AN and does not seem to be related to developmental maturation and some clinical features. Depression is probably the variable that best accounts for the variance in alexithymia, but is not a complete explanation for the known cognitive-affective disturbances in AN. Specific emotional competencies require scrutiny during psychiatric treatment.